Efeitos da dipirona, do meloxicam e da associação dipirona e meloxicam sobre a hemostasia em cães conscientes e sobre o controle da dor pós-operatória em cadelas submetidas à ovariosalpingohisterectomia - Zanuzzo, Felipe Sabbadin [UNESP] (2014)
In humans, dipyrone acts as a non-selective COX inhibitor and can inhibit platelet aggregation for up to 6 hours (1). Because dipyrone-induced analgesia may be attributable not only to its anti-inflammatory action, but also to its central nervous system mediated effects (2), this drug has been combined with other non steroid antinflammatories (NSAIDs), such as meloxicam, for the control of chronic pain in canine patients (3). Although the use of dipyrone alone or combined with meloxicam is theoretically justifiable, the analgesic benefits of this association and the potential adverse effects on hemostasis should be investigated before its clinical use is validated. In order to investigate the effects of dipyrone, meloxicam, and of the combination of these two drugs, the present study was carried out in 2 phases. During phase 1, presented in Chapter 1, the effects of a single dose administration of dipyrone, meloxicam, and of the combination of these two NSAIDs were evaluated on the hemostasis of conscious dogs. Six adult dogs were used in a prospective, randomized, crossover study. The animals received 4 treatments intravenously with 15-day washout intervals: control (0.1 mL/kg saline), meloxicam (0.2 mg/kg) dipyrone (25 mg/kg) and dipyrone combined with meloxicam (25 and 0.2 mg/kg respectively). Blood samples were collected for assessment of platelet aggregation in whole blood and thromboelastometry before, and 1, 2, 3, 5, and 8 hours after treatment administration. Buccal mucosal bleeding time was evaluated before and at 1, 3, and 5 hours of treatment administration. During phase 2 (Chapter 2), the postoperative analgesic effects promoted by a single dose of dipyrone, meloxicam, and of the drug combination were evaluated in bitches undergoing ovariohysterectomy in a prospective, randomized , double-blinded, placebo controlled study design. Forty healthy bitches selected for ovariohysterectomy were ...